2017
DOI: 10.12783/dtmse/icmea2015/7364
|View full text |Cite
|
Sign up to set email alerts
|

Flocculation Behavior of Starch Betainate

Abstract: Starch betainate was applied in flocculation of kaolin suspension. The flocculation efficiency of starch betainate increased with the increase of both DS and molecular weight of starch betainate, which demonstrated that the flocculation was realized mainly by charge neutralization and bridging of the particles. When the dose of crosslinked starch betainate with DS of 0.33 was 3ppm, the removal ratio of turbidity could reach 90.5%, which was similar to the effect of traditional etherified cationic starch. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…flocculation to a noticeable extent [92]. Similarly, Zhang et al [93] also found that highly substituted starch betainate (DS 0.32) improves the flocculation of a kaolin suspension, achieving a removal ratio of turbidity as high as 90%. Pal et al (2005) also studied the use of HCS for wastewater treatment, showing that a higher charge density results in higher energy dissipation rate, lower collision efficiency, lower restructure rate and stronger flocs in the flocculation system [72,94].…”
Section: Wet End Chemistrymentioning
confidence: 89%
“…flocculation to a noticeable extent [92]. Similarly, Zhang et al [93] also found that highly substituted starch betainate (DS 0.32) improves the flocculation of a kaolin suspension, achieving a removal ratio of turbidity as high as 90%. Pal et al (2005) also studied the use of HCS for wastewater treatment, showing that a higher charge density results in higher energy dissipation rate, lower collision efficiency, lower restructure rate and stronger flocs in the flocculation system [72,94].…”
Section: Wet End Chemistrymentioning
confidence: 89%